(untitled) (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: United Kingdom patients may be given brief advice about PA during health-related consultations and possibly referred to attend exercise on referral scheme. Evidence for in-house lifestyle clinics to educate patients about PA is limited. Think Active funded 10 primary care sites around Coventry to deliver lifestyle clinics offering education on health-related topics in a face-to-face, group workshop format over four weeks. Participants could be physically active after each clinic, e.g. allowed to walk close to the venue or chair-based exercise. Methods: Following ethical approval (P162725), this mixed-methods observational study comprised four work packages (WP). WP1. Survey: 97 attendees’ (F = 63, M = 34) PA, mental wellbeing, and other lifestyle behaviours were measured before the clinics started (baseline), on completion at four weeks (post), and one month following their completion at eight weeks (follow-up). WP2. Fidelity: Based on the brief provided, a list of criteria that clinics needed to follow was developed and each site was graded as low, medium, or high fidelity. WP3 and WP4. Semi-structured interviews: conducted using Teams/telephone to ascertain experiences and views of the leads who facilitated (n = 11; F = 9, M = 2) and patients (n = 11; F = 5; M = 6) who attended the lifestyle clinics. Results: Following data triangulation, consensus was reached on the plausibility that the lifestyle clinics: 1) increased PA behaviour; 2) increased readiness to change PA behaviour; 3) improved self-reported health; 4) improved mental wellbeing; 5) improved patients’ knowledge and understanding of PA, sedentary behaviour, diet, and nutrition. All sites were graded at least medium or high fidelity and whilst the patients and leads were very positive about their experience, issues and challenges unique to each of the sites were highlighted. Future Research: Due to a lack of control group, a feasibility RCT should now be conducted before assessing efficacy as part of a multi-site definitive trial. Conclusion: Attendees of the lifestyle clinics increased their PA and achieved mental health benefits. Despite areas for improvement being identified, the leads and patients had a positive experience. The lifestyle clinics should therefore be described as successful, thus guiding principles and a good practice document has been compiled.